Too much of two good things: Explicating the limited complementarity between drivers of MNC Headquarters’ absorptive capacity - Barakat, L. L.; Pedersen, T.; Amaral-Baptista, M.; Cretoiu, S. B.; Bento, P. (Management International Review, 2022)
This study examines how multinational corporation (MNC) knowledge management mechanisms (systems, coordination and socialization) and international exposure affect MNC headquarters’ absorptive capacity (AC). We build on Cohen and Lev- inthal’s (Admin Sci Quart 35(1):128–152, 1990, https://doi.org/10.2307/2393553) under-researched trade-off between the inward- and outward-looking drivers of AC in the context of the MNC international knowledge transfer. First, we hypothesize that knowledge management mechanisms (the inward-looking driver) and interna- tional exposure (the outward-looking driver) directly influence headquarters’ AC. Our findings from a sample of 106 Brazilian and Portuguese MNC headquarters support this view. Second, because "not-invented-here" syndrome and distance can affect knowledge flows from subsidiaries, we develop a hypothesis on the trade-off between AC’s inward- and outward-looking drivers. We observe that their impact on the AC of MNC headquarters is diminished for high levels of coordination mecha- nisms and international exposure. Hence, coordination mechanisms become less effective to absorb subsidiary knowledge as the MNC increases its international footprint. We also conclude that the headquarters of highly internationalized MNCs can regard socialization mechanisms as facilitators of the absorption of knowledge generated by subsidiaries.